Timoleague Franciscan Friary, north choir wall, tomb niche, capital - O'Donovan, Danielle (My University, 2008)
Capital of tomb niche jamb. From top down, moulding comprises: chamfered abacus, wave, roll, fillet, bell, roll.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Gothic capitals (Architecture); Late Medieval; bell capitals; roll moldings; fillets (moldings)